Clinical outcomes of patients with deferred revascularisation based on fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) negative coronary artery lesions in Pakistani population - Muhammad Nasir Rahman; Ali, Jamshed; Sheema Saadia; Adnan, Ghufran (Journal of the Pakistan Medical Association, 2024)
Objective: To assess long-term clinical outcomes and factors associated with target vessel revascularisation in patients with deferred revascularisation based on negative fractional flow reserve and negative instantaneous wave-free ratio. Method: The longitudinal, retrospective study was conducted from July 1, 2020, to January 1, 2022, at the Aga Khan University Hospital, Karachi, and comprised medical records from January 2012 to January 2020 of patients with deferred revascularisation having intermediate to severe coronary lesions on coronary angiogram and had negative fractional flow reserve >0.80 or instantaneous wave-free ratio >0.89 and had not undergone immediate or planned revascularisation on the basis of negative physiological assessment. Data was collected from the institutional records, while final follow-up was taken by reviewing the medical records or telephonic interviews regarding any major adverse cardiac event after the index procedure. Data was analysed using Stata 14.2. Results: Of the 345 patients, 245(71%) were males. The overall mean age was 62±11 years. There were 194(56%) patients who presented with stable angina and 151(44%) presented with acute coronary syndrome. Mean fractional flow reserve was 0.87±0.04 and mean instantaneous wave-free ratio was 0.93±0.03. Multivessel disease was present in 223(65%) patients. Median follow-up period was 29 months (IQR: 24-36 months). Major adverse cardiovascular events occurred in 22(6%) patients, and target vessel revascularisation was required in 11(3%). Diabetes and percentage of stenosis were found to be independent predictors of major adverse cardiovascular events (p<0.05). Conclusion: Deferral of revascularisation and opting for medical treatment for coronary artery stenosis with higher fractional flow reserve or instantaneous wave-free ratio could be considered a safe and reasonable strategy. Key Words: Fractional flow reserve, Instantaneous wave-free ratio, Deferred revascularisation, Target vessel revascularisation.